Soil erodibility calculations based on different particle size distribution measurements - Centeri, Csaba; Szalai, Zoltán; Jakab, Gergely; Barta, Károly; Farsang, Andrea; Szabó, Szilárd; Bíró, Zsolt (Hungarian Geographical Bulletin, 2015)
In this study we focused on the factors affecting final outputs of the USLE (Universal Soil Loss Equation) model. In doing so, we conducted soil particle size measurements in different institutions (University of Debrecen, University of Szeged and Geographical Institute, Research Centre for Astronomy and Earth Sciences of the Hungarian Academy of Sciences) with a variety of methodologies (laser, aerometer and pipette methods) on various soil materials (sandy, loamy and clay). Statistical analyses of the eight examined soil samples have been shown some significant and some non-significant differences among the particle size measurements. This paper is aimed at i) to ascertain whether these significant differences in particle size measurements cause significant differences in soil erodibility calculations; and ii) to assess the amount of soil loss calculated by these K factors. The results suggest that regardless of the relatively small percentage between the smallest and the greatest K factor values, the amount of soil loss can be fairly high, especially when erosion occurs on a longer or steeper slope. In the present case, when we compare simulations results, the amount of soil loss is more important than the difference in percentage between the minimum and maximum values. Because the percentage of the difference can remain the same between the simulations, while the amount of soil loss increases way beyond soil loss tolerance limits.